Encounters with History, Theory and Doctrine: Some Reflections on Discharge by Breach of Contract - PHANG, Andrew (Institutional Knowledge at Singapore Management University, 2015)
The topic of discharge by breach of contract constitutes one of the thorniest areas of the common law of contract. This paper is a wide-ranging one and adopts a comparative approach. It first explores the nature of a breach of contract (as contrasted, for example, to discharge of a contract by frustration) before proceeding to consider the relevant historical origins which might provide some clues as to why we now have different approaches in ascertaining whether or not the innocent party can elect to treat itself as discharged from a contract as a result of a breach by the other party of one or more of the terms of that contract (focusing on the “condition-warranty approach” and “Hongkong Fir approach”). The paper then proceeds to analyse the aforementioned approaches on doctrinal, theoretical as well as practical levels. Finally, it explores more specific aspects of the topic (including the legal effect of a breach of contract committed by both parties; whether termination of a contract of employment is “elective” or “automatic” (focusing on the UK Supreme Court decision of Geys v Société Générale, London Branch); as well as the breach of the implied term of mutual trust and confidence).